Jarīmah Sariqah dalam Hukum Pidana Islam: Analisis Unsur, Syarat, Perbandingan Mazhab, dan Relevansinya dengan KUHP Indonesia - Nihayatul Jannah; Akhmad Hafi; Siti Rahmah; Lahmudinur (PT. Pustaka Andil Lestari, 2025)
Theft is one of the most frequent criminal acts occurring within society and carries significant social and economic consequences. In Islamic criminal law, theft (sariqah) is classified as a jarīmah ḥadd, a criminal offense for which the sanction is explicitly determined by the Sharī‘ah. This study provides a comprehensive examination of the concept of theft in Islamic criminal law, including its definition, essential elements, legal conditions, and prescribed punishments. In addition, the study explores the relevance of applying Islamic criminal law to theft cases within the Indonesian social and legal context. The findings indicate that Islamic criminal law strongly emphasizes preventive measures, the protection of property rights, and the preservation of the five fundamental objectives of the Sharī‘ah (maqāṣid al-syarī‘ah). The implementation of firm punishments is intended not only to deter offenders but also to uphold moral and spiritual values, thereby contributing to the long-term security and order of society.